2012
DOI: 10.1258/ar.2011.110467
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lymphatic drainage to the mediastinum based on computed tomographic observations of the primary complex of pulmonary histoplasmosis

Abstract: Our data showed a predictable pattern of segmental and lobar lymphatic drainage to the mediastinum and suggested that skip involvement could represent the initial mediastinal node involvement via direct lymphatic drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Gorai et al 31 suggested that the incidence of skip N2 was significantly associated with pleural involvement in patients with clinical IA NSCLC and in those with nodal metastasis, and assumed an involvement of the subpleural lymphatic drainage. In addition, Takahashi et al 32,33 demonstrated a predictable pattern of lobar lymphatic drainage to the mediastinum by the assessment of CT studies of patients with primary complex histoplasmosis consisting of a single lobe pulmonary lesion and mediastinal nodal disease. They revealed that there were seven of 122 (5.7%) upper-lobe cases with skip SCLN involvement and 14 of 129 (10.8%) lowerlobe cases with skip UMLN involvement in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Gorai et al 31 suggested that the incidence of skip N2 was significantly associated with pleural involvement in patients with clinical IA NSCLC and in those with nodal metastasis, and assumed an involvement of the subpleural lymphatic drainage. In addition, Takahashi et al 32,33 demonstrated a predictable pattern of lobar lymphatic drainage to the mediastinum by the assessment of CT studies of patients with primary complex histoplasmosis consisting of a single lobe pulmonary lesion and mediastinal nodal disease. They revealed that there were seven of 122 (5.7%) upper-lobe cases with skip SCLN involvement and 14 of 129 (10.8%) lowerlobe cases with skip UMLN involvement in their study.…”
Section: Discussionmentioning
confidence: 99%